The 27 kDa Trypanosoma brucei Pentatricopeptide Repeat Protein is a G-tract Specific RNA Binding Protein. Issue 1 (December 2018) - Kamba, Pakoyo; Dickson, David; White, Neil; Ekstrom, Jennifer; Koslowsky, Donna; Hoogstraten, Charles
Abstract Pentatricopeptide repeat (PPR) proteins, a helical repeat family of organellar RNA binding proteins, play essential roles in post-transcriptional RNA processing. InTrypanosoma brucei, an expanded family of PPR proteins localize to the parasite's single mitochondrion, where they are believed to perform important roles in both RNA processing and translation. We studied the RNA binding specificity of the simplestT .brucei PPR protein (KRIPP11) using electrophoretic mobility shift assays, fluorescence anisotropy, circular dichroism spectroscopy, andin vitro selection. We found KRIPP11 to be an RNA binding protein with specificity for sequences of four or more consecutive guanosine residues (G-tracts). Such G-tracts are dramatically enriched inT .brucei mitochondrial transcripts that are destined for extensive uridine insertion/deletion editing but are not present in mRNAs following editing. We further found that the quadruplex oligoguanosine RNA conformation is preferentially recognized by KRIPP11 over other conformational forms, and is bound without disruption of the quadruplex structure. In combination with prior data demonstrating association of KRIPP11 with the small ribosomal subunit, these results suggest possible roles for KRIPP11 in bridging mRNA maturation and translation or in facilitating translation of unusual dual-coded open reading frames.